Antibacterial Activities of N-Hexan Ethyl Acetate Fraction and Water From Ethanol Extract of Yodium Leaves (Jatrophora Multifida L.) Against Pseudomonas Aeruginosa ATCC 27853 - Hikmah, Siti Nur; Setianto, Rony; Dewi, Belinda Arbitya; Utami, Rina (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The extraction of yodium leaf by maceration method used ethanol 70% solvent, followed by fractionation with n-hexana, ethyl acetate and water solvents. The antibacterial activity test performed by the diffusion method and dilusion method. Diffution method by consentration ethanol extracts and fraction are used 50%, 25% and 12,5%. Dilution method by consentration ethyl acetate fraction are used 50%, 25%, 12,5%, 6,25%, 3,125%, 1,5625%, 0,78125%, dan 0,390625%. The chemical contens of the most active fraction were tested by TLC. The results showed that the ethanol extract of yodium leaf (J. multifida), of n-hexana, ethyl acetate and water fraction had antibacterial activity against P. aeruginosa ATCC 27853. Ethyl acetate fraction was the most active fraction with an average of inhibition diameter at concentrations of 50% was 14,7 mm, concentration of 25% was 14,4 mm and concentration 12,5% was 11,7 mm. Minimum kill concentration ethyl acetate fraction against P.aeruginosa ATCC 27853 of 12,5%